An exploration of functional and numerical flexibility in South African organisations: a qualitative study in two textile factories in Cape Town - Sela, Ronit (Rhodes University, Faculty of Humanities, Department of Sociology and Industrial Sociology, 2002)
During this research, an attempt was made to gain an understanding of management and their employees' perceptions regarding functional and numerical flexibility practices within South African organisations. To achieve this, twenty-six people, comprising of a variability of positions within the organisation, were interviewed in the region of the Western Cape. It was found that, although extensive research on the two forms of flexibility have been globally conducted, South African literature, particularly on the part of numerical flexibility, is limited. It is thus believed that this study will present a valuable basis to pursue in further research. Literature that was consulted was found to be supportive of the theoretical notion that South African organisations, in order to be globally competitive, have had to restructure and redefine themselves by ensuring that they make the most efficient and effective use of their human resources. The study found that whilst functional flexibility practices benefit employees in that they experienced increased job satisfaction and job mobility, it was the area of numerical flexibility which raised many dissatisfactions, including those of immense job insecurity and remuneration, both financial and otherwise. The study findings suggest a need for a more comprehensive and employee integrated approach by combining organisational with individual oriented initiatives, and ensuring the trade union's involvement in all facets of functional and numerical flexibility initiatives. The thesis ends with recommendations of various strategies for addressing the concerns of management, employees and the trade union in order to ensure full and proper utilisation of human resources so that the end product, namely job satisfaction, leads to organisational success.
Keywords: Business enterprises -- South Africa -- Case studies; Industrial management -- South Africa